AD, Volume 29, n° 2, 2004 - Full Issue - Full issue, (Africa Development, 2004)
Contents Decentralisation, espaces participatifs et l'idée de l'indigénisation de l'Etat africain: le cas des communes maliennes Clemens Zobel .................................1 Re-inventing Federalism in Post-Transition Nigeria: Problems and Prospect Osita Agbu .........................................26 Rethinking East African Integration: From Economic to Political and from State to Civil Society Hannington Ochwada ..........................53 The Multiparty Promise Betrayed: The failure of Neo-Liberalism in Malawi Nixon S. Khembo ...............................80 Decentralisation and Development: The Malawian Experience Mustafa K. Hussein .................................106 Towards Better Management of Public Education in Cameroon: The Case for Decentralisation Joseph A. Tamukong .................................134 Book Review/Revue de livres Lilia Labidi, 2003, Romancières sénégalaises à la recherche de leur temps. Amadou Ly ....................................158